Environmental awareness and participation of Filipino pre-service teachers - Lualhati, Genalyn P. (JPBI (Jurnal Pendidikan Biologi Indonesia), 2019)
Schools are accountable to cultivate environmental awareness and participation among future leaders. In an attempt to address this concern, this research determined the level of environmental awareness and involvement of teacher education seniors in one state university in the Philippines. Specifically, it focused on the respondents' level of environmental awareness in terms of issues and policies and level of environmental participation in terms of waste management, resource conservation, and environmental initiative. By employing the descriptive method of research with self-made questionnaire as its gathering tool. This paper found out that the respondents were unaware of environmental issues and policies, while they were moderately participative in activities relevant to environmental protection and conservation. With the findings of the study, enrichment activities offered by the researcher as well as considered by concerned authorities for its maximum actualization to enliven the once-perfect the environment which human beings continuously destroy.